FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KURANG ENERGI KRONIS (KEK) PADA IBU HAMIL DI PUSKESMAS PAAL X KOTA JAMBI - Ruwayda, Ruwayda; Sartika, Jumiati (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2024)
ABSTRACT Background: The incidence of Chronic Energy Deficiency (CED) tends to increase every year according to data from the Jambi City Health Office in 2018 showing that pregnant women with Chronic Energy Deficiency were 6% of 11,581 pregnant women and in 2019 it increased by 7% of 11,680 pregnant women. CED has an impact on increasing the risk of anaemia, bleeding, infection, risk of prolonged and premature delivery. Methods: Observational research with cross sectional design at Primary Health Care Paal X, Jambi City. Aiming to determine the factors associated with the incidence of Chronic Energy Deficiency in pregnant women. The population of all pregnant women who did pregnancy checks was 164 people. The sample was taken by quota sampling as many as 61 people. Data collection using a questionnaire. Univariate analysis and bivariate chi-square test. Results: A total of 36.1% of pregnant women with CED. There is a relationship between education level (p=0.015), knowledge (p=0.032), occupation (p=0.045) with the incidence of CED. There was no association of age (p=0.775), and income (p=0.276) with the incidence of CED. Conclusion: Several factors are associated with the incidence of CED pregnant women, namely education, knowledge and occupation. It is hoped that health workers will improve the program of handling pregnant women with CED through nutritional needs counselling and early detection of factors that cause CED in pregnant women.